PENGEMBANGAN DAN IMPLEMENTASI METODE FUZZY MAMDANI UNTUK PENILAIAN KINERJA PENELITIAN DOSEN - Alwendi Alwendi; Khairunnisa Samosir (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2023)
Today, information technology, especially soft computing technology is growing rapidly. One of the soft computing technologies that has been widely developed is fuzzy logic. This is because it can be used to measure various phenomena that are unclear, obscured or obscured. One of the research themes that uses fuzzy logic is the assessment system in research. Research [Graha Nusantara Padangsidimpuan Data Simlitabmas Still in the Leadership category for promotion to the Madya Faculty of UGN Padangsidimpuan is challenged to develop, dedicate and apply the knowledge needed in research. To do this, an application that can be used to calculate and record the results of lecturers in learning. The goal according to this research is to apply fuzzy reasoning with the Mamdani method for lecturer research activities at the University of Graha Nusantara Padangsidimpuan. This research uses Mamdani fuzzy logic. The Mamdani fuzzy method is a way to convert the input space to the output space.